Active Galactic Nucleus Jet-inflated Bubbles as Possible Origin of Odd Radio Circles - Yen-Hsing Lin; H.-Y. Karen Yang (The Astrophysical Journal)
Odd radio circles (ORCs) are newly discovered extragalactic radio objects with an unknown origin. In this work, we carry out three-dimensional cosmic-ray (CR) magnetohydrodynamic simulations using the FLASH code and predict the radio morphology of end-on active galactic nucleus (AGN) jet-inflated bubbles considering hadronic emission. We consider CR proton (CRp)-dominated jets as they tend to inflate oblate bubbles, promising to reproduce the large inferred sizes of the ORCs when viewed end-on. We find that powerful and long-duration CRp-dominated jets can create bubbles with similar sizes (∼300–600 kpc) and radio morphology (circular and edge-brightened) to the observed ORCs in low-mass ( M _vir ∼ 8 × 10 ^12 − 8 × 10 ^13 M _⊙ ) halos. Given the same amount of input jet energy, longer-duration (thus lower-power) jets tend to create larger bubbles since high-power jets generate strong shocks that carry away a significant portion of the jet energy. The edge-brightened feature of the observed ORCs is naturally reproduced due to efficient hadronic collisions at the interface between the bubbles and the ambient medium. We further discuss the radio luminosity, X-ray detectability, and the possible origin of such strong AGN jets in the context of galaxy evolution. We conclude that end-on CR-dominated AGN bubbles could be a plausible scenario for the formation of ORCs.